Effects of atmospheric plasma treatment on adhesion and tribology of aromatic thermoplastic polymers. (16th September 2017) - Al‐Maliki, Hayder; Zsidai, László; Samyn, Pieter; Szakál, Zoltán; Keresztes, Róbert; Kalácska, Gábor
Abstract : After cold plasma treatment of poly(ethylene terephthalate) and poly(ether‐ether ketone) surfaces by dielectric barrier discharge (DBD) under atmospheric (air) conditions, variations in surface chemistry, and morphology were investigated in relation with adhesion and tribological properties. According to XPS measurements, surface oxidation caused the formation of low molecular weight moieties of carboxylic acids. The latter resulted in more hydrophilic surfaces according to water contact angle measurements, with mainly a higher polar surface energy component. In parallel, the surface roughness of originally polished surfaces reduced due to flattening of local surface asperities after DBD. The DBD significantly improved the adhesive shear strength for different glue types in polymer/polymer and polymer/steel joints, while the best adhesion was observed for a two‐component epoxy type adhesive. Under dry sliding conditions, the coefficients of friction were lower after DBD compared to pristine samples only under mild sliding conditions ( v = 0.05 m/s; p < 1 MPa.m/s), while the higher normal loads caused an increase in coefficients of friction likely due to the higher contributions of surface deformation. Most interestingly, the lower coefficients of friction after DBD were observed under oil lubrication and after cleaning the sliding track ("run‐out" condition), due to the better retention of oil at the sliding surface for plasma‐treated polymers. POLYM. ENG. SCI., 58:E93–E103, 2018. © 2017 Society of Plastics Engineers